Analisis Manajemen Kurikulum Sebagai Upaya Pendidikan Karakter di Madrasah Aliyah Al-Washliyah 49 Pasar Lembu - Neliwati; Mhd Joni Marpaung; Afifah Thaiyibah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to analyze the curriculum management at Madrasah Aliyah Alwashliyah 49 Pasar Lembu and the extent to which it contributes to the effort to improve character education. Through a review of curriculum management, this research explores the extent to which management theory is applied in the context of character education in the school. The analysis method involves collecting data from various sources, including official documents, observations, and interviews with stakeholders. The results of the analysis highlight the importance of integrating character education into every aspect of curriculum management, from planning, implementation, to evaluation. Furthermore, the findings also indicate efforts to develop human resources, culture, and community as an integral part of curriculum management to support the improvement of character education. The implications of this analysis are expected to contribute to the development of more effective curriculum management strategies in improving character education in the Madrasah Aliyah Alwashliyah 49 Pasar Lembu environment.